Ocular Toxoplasmosis: Therapy-Related Adverse Drug Reactions and Their Management - Helfenstein, M.; Zweifel, S.; Barthelmes, D.; Meier, F.; Fehr, J.; Böni, C. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background There are different treatment options for ocular toxoplasmosis (OT). “Classic” therapy consists of pyrimethamine, sulfadiazine and folinic acid combined with systemic steroids and is still widely used. However, potentially severe side effects of this therapy have been reported. The aim of this retrospective study was to evaluate the incidence and types of adverse drug reactions in patients treated for OT. Clinical management of each adverse drug reaction was assessed. Patients and Methods In this retrospective analysis, we reviewed data of patients with OT, who were consecutively examined between December 2011 and December 2015 at the Department of Ophthalmology, University Hospital Zurich. Results In total, 49 patients had at least one episode of active OT. In 54 (83.0 %) of 65 treated episodes, the classic regimen was used. Of the 37 patients who received classic treatment, 9 (24.3 %) developed at least one adverse drug reaction which led to drug discontinuation, including elevated creatinine (5.4 %), elevated liver enzymes (5.4 %), vomiting (5.4 %), rash (5.4 %) and facial swelling (2.7 %). In 5 patients, treatment was switched to another drug, while in the other 4 patients, therapy was stopped. In these 9 patients, inflammation was well controlled 8 weeks after onset of therapy. No patient suffered from severe side effects, such as potentially life-threatening allergic reactions or pancytopenia. Conclusions In OT patients who were treated with classic therapy, adverse drug reactions are common. Therefore, clinical and laboratory monitoring is mandatory. Adverse drug reactions may require interdisciplinary management.
Keywords: Ocular toxoplasmosis; sulfadiazine; pyrimethamine; adverse drug reactions